Some Factors which Promote and Restrict Islamization in America - Akbar Muhammud (International Institute of Islamic Thought, 2021)
Let me begin with a brief explicatory statement about the word ‘Islamization.’ I use this term here in reference to a two-stage process. The first stage is conversion to Islam,’ and the second is the reinforcement, strengthening or deepening of Islam in the individual. Of course, most Muslims in the world are born into a Muslim family, and thus they do not pass through the first stage, or so it would seem. But many of them do have social, intellectual and spiritual experiences which are the essence of the second stage of Islamization. An example of this would be the effects of the international phenomenon called “the resurgence of Islam”. In America, the situation is somewhat different. Recent immigrants from Muslim societies-say during the last eighty years-and their offspring generally do not pass through the first stage per se. However, American Muslims, who are descendants of people who arrived here from Europe (European-Americans or “white Americans”) and Africa (African-Americans or “black Americans”) several centuries ago, passed through, in varying degrees, both stages. Now let us consider some factors which promote and restrict Islamization in America ...